Digestão anaeróbia de resíduos de frutas e verduras: estratégias para minimizar efeitos na fase de hidrólise - Gomes, Marianna Câmara (2022)
With the economic growth and the urbanization process, large urban centers face challenges in the management of organic solid waste related to final disposal, which is mainly composed of food waste, fruits and vegetables waste. Normally, the final destination of the organic fraction of municipal solid waste (OFMSW) is in landfills; however, fruit and vegetable waste (FVW) has high moisture content and biodegradability, which can increase the emission of greenhouse gases and the volume of leachate produced in the landfill. Therefore, biological processes such as anaerobic digestion (AD) is a promising alternative for energy and nutrient recovery from FVW. In addition, with the production of biogas and biofertilizer, it is possible to minimize the impacts of the energy and fertilizer crisis. On the other hand, the AD of these wastes has a major limitation in the hydrolysis phase, due to easily hydrolyzable carbohydrates, causing a drop in pH and low biogas production due to accumulation of volatile fatty acids (VFAs). Thus, the objective of this work was to evaluate the influence of different strategies in AD of FVW, in order to minimize the effects of the hydrolysis phase, as well as the efficiency and stability of the process in batch and semicontinuous trials. The batch assay was conducted in 6.0 L reactors, with 4.5% total solids and room temperature, for 200 days. Four treatments with four repetitions each were evaluated, differing the particle size of the substrate in 3, 2, 1 and <0.5 cm, to observe the performance of this parameter in the AD. The semi-continuous assay was conducted in plug flow reactors of 60.0 L at mesophilic temperature, with a 30-day hydraulic retention time. Four treatments were evaluated in four reactors, open hydrolysis system, thermal pre-treatment at 70 °C, association of open hydrolysis and thermal pre-treatment and a control treatment without a strategy to minimize the effects of the hydrolysis phase, daily feed containing 3, 3, 2 and 3.5%ST, respectively (2.0 L of which 60% was water and 40% biofertilizer recycle). The batch treatment with smaller particle size provided the highest specific production of biogas (p<0.05) (0.09 m³ kgVS-1 ) and biohydrogen (0.04 m³H2 kgVS-1 ), with consumption of 88.94% of total carbohydrates and lower accumulation of VFAs. Therefore, the reduction in particle size increased the surface area available to the microorganisms. In the semi-continuous assay, the thermal pre-treatment at 70 °C showed an increase of 24.24% in methane content, with the highest specific production of biogas (p<0.05) (0.76 m³ kgVS-1 ) and methane (0.41 m³CH4 kgVS-1 ), besides lower accumulation of VFA (0.34 g L-1 ) and better nutrient recovery through biofertilizer.